"Work for their prime, the workhouse for their age": Old Age Pauperism in Victorian England. Issue 1 (25th January 2016) - Boyer, George R.
Abstract : This paper examines the extent of local government support for the elderly, in the form of poor relief, in Victorian England. It presents newly constructed estimates of old age pauperism rates for each of England's ten registration divisions from 1861 to 1908, the year the Old Age Pension Act was adopted. My estimates show that the share of persons aged 65 and older receiving government assistance in the nineteenth century was far larger than most contemporaries, and many historians, believe. The share receiving poor relief declined after 1871, largely as a result of changes in relief administration, but on the eve of the adoption of the Old Age Pension Act more than one in five persons over 65 was in receipt of public assistance. In sum, government support for the elderly is not a post-welfare state phenomenon. Old age pauperism rates differed substantially across registration divisions and in general were higher in southern than in northern England. I present evidence that much of the north-south differential was due to differences in wage rates and employment opportunities and differences in the administration of poor relief, although differences in welfare customs might have played a role.